Health-Related Quality of Life and Sociodemographic Characteristics as Prognostic Indicators of Long-term Survival in Disease-Free Cervical Cancer Survivors. Issue 4 (May 2016) - Kim, Mi-Kyung; Sim, Jin Ah; Yun, Young Ho; Bae, Duk-Soo; Nam, Joo Hyun; Park, Chong Taik; Cho, Chi-Heum; Lee, Jong-Min; Park, Sang Yoon
Abstract : Objectives: Health-related quality-of-life (HRQOL) issues of cancer patients are considered an important clinical outcome. We aimed to investigate the prognostic value of HRQOL on long-term survival outcomes in disease-free cervical cancer survivors (CCSs). Methods: The study sample consisted of 860 disease-free CCSs from 6 Korean cancer hospitals recruited for HRQOL survey during 2005 (median time from diagnosis, 5.9 years). Health-related quality-of-life measures included the European Organization for Research and Treatment of Cancer QLQ-C30 and its Cervical Cancer Module (CX24). Survival data were retrieved from the Korean Statistical Office after 6 years from the survey. Health-related quality-of-life domains along with sociodemographic and clinicopathologic variables were analyzed as prognostic factors for survival from the date of survey. Results: During the median follow-up period of 6.3 years after the survey, 30 (3.5%) patients died from all causes. Age, time since diagnosis, and physical activity were independent prognostic factors, which constituted the baseline model along with cancer stage. When HRQOL domains were tested separately against the baseline model, functional scales (physical, role, social, and emotional functioning), global health status, symptom scales (pain and appetite loss), and cervical cancer module items (body image, sexual inactivity, and sexual worry) were significantly associated with survival ( P < 0.05). Conclusions: These findings suggest that, in addition to well-known prognostic factors, including age, time since diagnosis, and physical activity, HRQOL scores obtained from disease-free CCSs are associated with survival.